Molecular Characterization of a Gene Encoding Insulin-Like Peptide 5 (ILP5) in Drosophila virilis - Nikolas R Likourentzos; Jae H. Park (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2020)
The study of the insulin-like peptides of Drosophila can provide insight of their similarities to mammalian insulin and their potential usage in treating human insulin-related diseases. In this study, we isolated and characterized cDNA encoding insulin-like peptide (ILP) 5 in D. virilis by using RNA purification, reverse transcription, and RACE protocols. Subsequently, various bioinformatic softwares were employed to predict peptide structure. The ILP5 gene (587 base pairs) codes for 121 amino acids that make up prepro-ILP5. After maturation, functional ILP5 is a peptide of two 25 amino acid chains, A- and B-chain, connected by two disulfide bonds. Sequencing genomic DNA of the D. virilis ILP5 gene identified an intron within the gene. The peptide sequence of D. virilis ILP5 shows similarities to other ILPs of Drosophila and the predicted structure to mammalian insulin, supporting that the cysteine residues of the insulin peptide are necessary for the function of the peptide in all organisms.
Keywords: Drosophila; insulin; insulin-like peptide 5; gene sequencing; peptide prediction; diabetes